The Effect Of Role Play Strategy In Teaching Vocabulary At The Eighth Grade Of SMP Negeri 5 Pematang Siantar - Eka Ria Oktavia Ginting Munthe; Yanti kristina Sinaga; Christian Neni Purba (CV Putra Publisher, 2023)
The aim of this research is to look at The Effect Of Role Play Strategy In Teaching Vocabulary At The Eighth Grade Of Smp Negeri 5 Pematang Siantar. This research would employ a quasi-experimental design with a quantitative research and a